Coupled thermal–structural analysis and multi-objective optimization of a cutting-type energy-absorbing structure for subway vehicles. (August 2019) - Wang, Junyan; Lu, Zhaijun; Zhong, Mu; Wang, Tianjun; Sun, Chengming; Li, Haihong
Abstract: With the aim of improving passive safety protection in subway vehicles, this paper investigates a cutting energy-absorbing structure by means of experiment and simulation. The proposed structure comprises a cutting knife, an energy-absorbing tube, and a support tool. The Johnson-Cook material model is used to study the coupled thermal–structural cutting energy-absorbing process, and a finite-element model of the cutting energy-absorbing structure is validated using data from a cutting collision experiment. The sensitivity of each factor is discussed using extreme difference analysis to identify the effects of the cutting depth, cutting width, and cutting knife rake angle on the energy absorbed ( EA ) and the peak cutting force ( PCF ). Based on sample points obtained from an optimal Latin-hypercube experimental design, a relationship between the crashworthiness index and the design variables is formulated using polynomial-response-surface and radial-basis-function surrogate models. Through comprehensive error analysis, the most accurate surrogate model is used to optimize the crashworthiness of the structure. The multi-objective particle swarm optimization algorithm is applied to multi-objective optimization to obtain the maximum EA and minimum PCF . The weighting factor plays an important role in selecting the ideal Pareto solution, and the optimal solution is determined using the minimum distance selection method. The results allow us to determine the structure with the best crashworthiness, for which EA  = 991 kJ and PCF  = 1441 kN. Highlights: Present a cutting energy absorption structure for used in subway vehicles. The coupled thermal–structural method is used to analysis the crashperformance of the cutting absorption energy structure. The results of simulations are in good agreement with the experimental results. The multi-objective optimization of cutting energy absorption structure is carried out by two surrogate models. The MOPSO algorithm is used to obtain the optimal parameters of the cutting energy absorption structure.